From Solow to Romer: Teaching endogenous technological change in undergraduate economics. (January 2018) - Chu, Angus C.
Abstract: Undergraduate students learn economic growth theory through the seminal Solow model, which takes the growth rate of technology as given. To understand the origin of technological progress, we need a model of endogenous technological change. The Romer model fills this important gap in the literature. However, given its complexity, undergraduate students often find the Romer model difficult. This paper proposes a simple method of teaching the Romer model. We add three layers of structure (one at a time) to extend the familiar Solow model into the less familiar Romer model. First, we incorporate a competitive market structure into the Solow model. Then, we modify the competitive market structure into a monopolistic market structure. Finally, we introduce an R&D sector that invents new products.